Drug review: mTOR-inhibitor therapy in fetal cardiac rhabdomyoma—a tightrope walk - Muschel, Nadine; Höck, Michaela; Griesmaier, Elke; Azim, Samira Abdel; Ralser, Elisabeth; Schreiner, Christina; Schermer, Elisabeth; Kiechl-Kohlendorfer, Ursula; Mutz-Dehbalaie, Irene; Michel, Miriam (Frontiers in Pediatrics, 2025)
ObjectiveMechanistic/mammalian target of rapamycin (mTOR) inhibitors have been used successfully to reduce the size of cardiac rhabdomyomas. However, the number of published cases is small and thus there is no consensus about therapeutic approaches, especially regarding dosing regimens and safety profiles of mTOR inhibitors. Based on a systematic literature review and one new case report, we discuss in detail the indication and adverse effects of fetal and neonatal mTOR-inhibitor therapy.MethodsA comprehensive search was conducted on PubMed/MEDLINE and Web of Science for studies using combinations of the relevant medical subject heading (MeSH) terms and keyword (rhabdomyoma AND fetal OR fetus OR prenatal AND cardiac AND sirolimus) from the first report in 2018 until July 2025. Studies were included if they reported on pregnancies with fetal cardiac tumor and rhabdomyoma entity suspicion treated with mTOR inhibitors.Results of literature review and new case descriptionIn total, 67 results were found. After excluding non-eligible publications, a total of 20 documented cases were identified from 15 reports, all presenting lifesaving effects of mTOR inhibitors in fetuses and neonates with cardiac rhabdomyomas. We report on a patient with a prenatally suspected cardiac rhabdomyoma, which, due to imminent bilateral outflow tract obstruction, was prenatally treated with sirolimus. Tumor regression could be achieved. For maternal medical reasons, prenatal sirolimus had to be stopped after 5 weeks. Postnatal incessant atrioventricular re-entrant tachycardia occurred, which was unresponsive to electric or medical cardioversion (amiodarone) and unresponsive to everolimus. The patient developed massive capillary leak syndrome within hours. In combination with restrictive ventricular filling properties, the tachycardia resulted in death on the seventh day of life.ConclusionCardiac rhabdomyomas have the potential to become a life-threatening condition, not only by impairing myocardial function and cardiac outflow, but also by causing arrhythmia due to tumor muscle bundles as substrate for a pre-excitation syndrome resulting in intrauterine or postnatal atrioventricular re-entrant tachycardia, as observed in our patient. The pharmacological therapeutic approach is fetal and neonatal treatment with mTOR inhibitors. All previous reported cases present lifesaving effects of mTOR inhibitors in fetuses and neonates with cardiac rhabdomyomas; however, adverse effects cannot be disregarded.